STRATEGI PENGEMBANGAN DAYA TARIK WISATA DESA WATURAKA, KABUPATEN ENDE, FLORES - Kupertino Ilang, Yosep; Darma Putra, I Nyoman; Sunarta, I Nyoman (Jurnal Master Pariwisata (JUMPA); Volume 04, Nomor 02, Januari 2018DO - 10.24843/JUMPA.2018.v04.i02.p10, 2018)
Waturaka Village, East Nusa Tenggara Province, has a rich tourist attractions, but they have not been managed optimally. Thi article analyses the village tourism potential and set strategies to develop tourist attarctions of the village. Data collection was conducted through observation, interview, and documentation study. Interview was conducted with as many as 25 people and was divided into four categories including representative of government o cers, NGO activists, members of tourism awareness group (Pokdarwis), and villagers. Data were analyzed by using SWOT techniques (Strength, Weakness, Opportunities, Threat). The results shows that the main potential tourist attractions are Murukeba Waterfall and agro- tourism and the development is in the involvement stage. S-O strategy (Strength-Opportunities) is applied by using strength to take advantage of opportunities. ST Strategy (Strength- Threat) is applied by utilizing strength to overcome the threat. WO (Weakness-Opportunities) strategy is applied to minimize the weaknesses to take advantage of opportunities. WT strategy (Weakness-Threat) is conducted to minimize weaknesses to avoid threats.